Detection of Cryptosporidium oocysts in calves and children in Mosul, Iraq: Tawfiq I. Al-alousi1 and Omaima I. Mahmood - Al-alousi, Tawfiq I. (The Iraqi Journal of Veterinary Medicine, 2012)
This study was carried out during May-October 2010 to determine the prevalence of Cryptosporidium spp. in calves and children in rural areas around Mosul, north of Iraq. A total of 78 faecal samples were taken from calves which were no more than one year old. Information about age, consistency of faeces (as diarrheic or normal) and contact with human were recorded. At the same time, 95 stool samples were taken from children aged one month to 12 years old suffering from diarrhea and living in the same farms where the samples of calves have been collected. All samples were stained with modified Ziehl-Neelsen acid-fast stain and Auramine O techniques to detect the presence of Cryptosporidium oocysts. Results revealed that the prevalence of Cryptosporidium in calves and children were 43.56% and 18.9%, respectively. Comparison of results obtained with the two stain techniques showed no significant difference and being sensitive.